Extending Corporate Social Responsibility Research to the Human Resource Management and Organizational Behavior Domains: A Look to the Future. Issue 4 (24th October 2013) - Morgeson, Frederick P.; Aguinis, Herman; Waldman, David A.; Siegel, Donald S.
Abstract : Although issues of corporate social responsibility (CSR) have become an important topic of research, there have been few studies on this topic conducted in the fields of human resource (HR) management and organizational behavior (OB). To address this gap, we edited a special issue of Personnel Psychology that explicitly focuses attention on CSR in the HR/OB domains. In this introductory editorial, we synthesize and extend the four articles published in the special issue. We also address issues relating to the conceptualization and measurement of CSR, the application of microlevel theories to CSR, and the practical and methodological implications of research in this domain. Finally, we provide suggestions for future research linking CSR with some of the most frequently studied topics in HR/OB. We propose that a focus on HR/OB will improve our understanding of the antecedents and consequences of CSR and also benefit HR/OB in terms of bridging the science–practice and micro–macro gaps.